Survey on currently applied interventions in neonatal resuscitation (SCIN): A study protocol - Eckart, Falk; Kaufmann, Maxi; O’Donnell, Colm P. F.; Mense, Lars; Rüdiger, Mario (Frontiers in Pediatrics, 2023)
Introduction – Around 140 million children are born every year and post-natal transition is uncomplicated in the vast majority. However, around 5 to 15% of neonates receive supportive interventions during transition. Recent data on the interventions used is scarce. More data on the frequencies with which these interventions are used is needed to evaluate neonatal resuscitation, guide recommendations and to generate hypotheses for further research. The following protocol describes an international, multicentre survey on the interventions currently applied during neonatal resuscitation. Objectives – To determine the frequencies at which different supportive interventions recommended by European Resuscitation Council (ERC) guidelines for neonatal resuscitation are used. To compare the frequencies between hospitals and patient groups and to investigate possible factors influencing any differences found. Methods – Participating hospitals will collect data on all interventions performed during neonatal resuscitation over a period of 6 months. All hospitals providing perinatal care are eligible regardless of size and designated level of neonatal care. Every neonate requiring more interventions than basic drying and tactile stimulation during the first 30 minutes of life will be included. The targeted sample size is at least 4000 neonates who receive interventions. After anonymization, the data is pooled in a common database and descriptive and statistical analysis is performed globally and in subgroups. Possible correlations will be investigated with phi coefficient and chi square testing. Ethics and dissemination – Consent of the institutional review board of the Technical University Dresden was obtained for the local data collection under the number BO-EK-198042022. Additionally, approval of local ethical or institutional review boards will be obtained by the participating hospitals if required. Results will be published in peer-reviewed journals and presented at suitable scientific conferences.